Toxocariasis diagnosed in international travelers at the Institute of Tropical Medicine, Antwerp, Belgium, from 2000 to 2013. - Steven Van Den Broucke; Kirezi Kanobana; Katja Polman; Patrick Soentjens; Marc Vekemans; Caroline Theunissen; Erika Vlieghe; Marjan Van Esbroeck; Jan Jacobs; Erwin Van Den Enden; Jef Van Den Ende; Alfons Van Gompel; et al. (Public Library of Science (PLoS), 2015)
Although infection with Toxocara canis or T. catis (commonly referred as toxocariasis) appears to be highly prevalent in (sub)tropical countries, information on its frequency and presentation in returning travelers and migrants is scarce. In this study, we reviewed all cases of asymptomatic and symptomatic toxocariasis diagnosed during post-travel consultations at the reference travel clinic of the Institute of Tropical Medicine, Antwerp, Belgium. Toxocariasis was considered as highly probable if serum Toxocara-antibodies were detected in combination with symptoms of visceral larva migrans if present, elevated eosinophil count in blood or other relevant fluid and reasonable exclusion of alternative diagnosis, or definitive in case of documented seroconversion. From 2000 to 2013, 190 travelers showed Toxocara-antibodies, of a total of 3436 for whom the test was requested (5.5%). Toxocariasis was diagnosed in 28 cases (23 symptomatic and 5 asymptomatic) including 21 highly probable and 7 definitive. All but one patients were adults. Africa and Asia were the place of acquisition for 10 and 9 cases, respectively. Twelve patients (43%) were short-term travelers (< 1 month). Symptoms, when present, developed during travel or within 8 weeks maximum after return, and included abdominal complaints (11/23 symptomatic patients, 48%), respiratory symptoms and skin abnormalities (10 each, 43%) and fever (9, 39%), often in combination. Two patients were diagnosed with transverse myelitis. At presentation, the median blood eosinophil count was 1720/μL [range: 510-14160] in the 21 symptomatic cases without neurological complication and 2080/μL [range: 1100-2970] in the 5 asymptomatic individuals. All patients recovered either spontaneously or with an anti-helminthic treatment (mostly a 5-day course of albendazole), except both neurological cases who kept sequelae despite repeated treatments and prolonged corticotherapy. Toxocariasis has to be considered in travelers returning from a (sub)tropical stay with varying clinical manifestations or eosinophilia. Prognosis appears favorable with adequate treatment except in case of neurological involvement.